Diffusion tensor magnetic resonance imaging at 3.0 tesla shows subtle cerebral grey matter abnormalities in patients with migraine. Issue 5 (13th April 2006) - Rocca, M A; Ceccarelli, A; Falini, A; Tortorella, P; Colombo, B; Pagani, E; Comi, G; Scotti, G; Filippi, M
Abstract : Background and objective: Diffusion tensor (DT) magnetic resonance imaging (MRI) has the potential to disclose subtle abnormalities in the brain of migraine patients. This ability may be increased by the use of high field magnets. A DT MRI on a 3.0 tesla scanner was used to measure the extent of tissue damage of the brain normal appearing white (NAWM) and grey matter in migraine patients with T2 visible abnormalities. Methods: Dual echo, T1 weighted and DT MRI with diffusion gradients applied in 32 non-collinear directions were acquired from 16 patients with migraine and 15 sex and age matched controls. Lesion load on T2 weighted images was measured using a local thresholding segmentation technique, and brain atrophy assessed on T1 weighted images using SIENAx. Mean diffusivity and fractional anisotropy histograms of the NAWM and mean diffusivity histograms of the grey matter were also derived. Results: Brain atrophy did not differ between controls and patients. Compared with healthy subjects, migraine patients had significantly reduced mean diffusivity histogram peak height of the grey matter (p = 0.04). No diffusion changes were detected in patients' NAWM. In migraine patients, no correlation was found between T2 weighted lesion load and brain DT histogram derived metrics, whereas age was significantly correlated with grey matter mean diffusivity histogram peak height (p = 0.05, r  = −0.52). Conclusions: DT MRI at high field strength discloses subtle grey matter damage in migraine patients, which might be associated with cognitive changes in these patients.